The interaction of coherent acoustic phonons with electrons in semiconductor superlattices - Poyser, Caroline Louise (2015)
This thesis presents a study of the electron-phonon interaction in an n-doped weakly coupled semiconductor superlattice (SL). Two experiments were performed which studied different aspects of this interaction. Firstly, a coherent phonon optics chip was designed. This was used in an experiment where a phonon beam was passed through the SL while an electrical bias was applied to it. The experiment provided a sensitive measurement of the effects caused by bias in the SL on the phonon beam. Secondly, a train of strain pulses was passed through the SL and the charge transferred in the device due to the strain was investigated.